Dietary Bacillus NP5 supplement impacts on growth, nutrient digestibility, immune response, and resistance to Aeromonas hydrophila infection of African catfish, Clarias gariepinus (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Putra AN, Mustahal, Syamsunarno MB, Hermawan D, Fatimah DG, Putri PB, Sevia, Isnaini R, Herjayanto M. 2021. Dietary Bacillus NP5 supplement impacts on growth, nutrient digestibility, immune response, and resistance to Aeromonas hydrophila infection of African Catfish, Clarias gariepinus. Biodiversitas 22: 253-261. This study aims to investigate the effects of Bacillus NP5 supplementation as a probiotic on growth, immune response, and resistance of African catfish to Aeromonas hydrophila infection. Catfish with an initial weight of 6.8 ± 0.1 g were fed with different doses of Bacillus NP5 (0%, 1.1%, 1.2% B, 1.3%, and 1.4%) with three replications and reared for 60 days. The first 45 days were used to observed growth performance, and the last 15 days were used to perform challenge tests against A. hydrophila infection. The results showed that the treatment of 1.2% Bacillus NP5 results in the highest specific growth rate (2.55±0.28 day-1) and increased protein and lipid digestibility significantly (P
Keywords: African catfish, Bacillus NP5, growth, probiotic, response immune